A stable metal–organic framework with well‐matched pore cavity for efficient acetylene separation. Issue 5 (2nd March 2021) - Chen, Yang; Du, Yadan; Wang, Yong; Krishna, Rajamani; Li, Libo; Yang, Jiangfeng; Li, Jinping; Mu, Bin
Abstract: Acetylene, an important petrochemical feedstock, is the starting chemical to produce many polymer products. Separating C2 H2 from its by‐product mixtures is still an energy‐consuming process and remains challenging. Here, we present a metal–organic framework[Zn2 (bpy)(btec)], with a desirable pore geometry and stable framework, which demonstrated a high separation performance of C2 H2 from simulated mixtures. With the desirable pore dimension and hydrogen bonding sites, Zn2 (bpy)(btec) shows by far the both highest C2 H2 /C2 H4 and C2 H2 /CO2 uptake ratios, very high adsorption selectivities and moderately C2 H2 uptake of 93.5 cm 3 /cm 3 under 298 K and 1 atm. Not only straightforwardly produced high purity of C2 H4, but also recovered high purity of C2 H2 (>98%) in the regeneration process (>92% recovery). More notably, Zn2 (bpy)(btec) can be straightforwardly synthesized at a large scale under environmentally friendly conditions, and its good water/chemical stability, thermostability, and cyclic stability highlight the promise of this molecular sieving material for industrial C2 H2 separation.